Digital Marketing Strategy in Increasing Brand Awareness of MSME Local Products - Bagus Yunianto Wibowo; Nanang Adie Setyawan; Destine Fajar Wiedayanti (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose - This study aims to analyze the role of digital marketing strategies in increasing the brand awareness of local MSME products in the digital era and to provide effective strategy recommendations for business actors. Methodology - This study uses a descriptive qualitative approach by collecting data through in-depth interviews, observations, and documentation of MSME actors selected through purposive sampling. Data analysis was conducted using the Miles interactive model, with validation through the triangulation of sources and methods. Finding - Digital marketing has been proven to significantly contribute to increasing the brand awareness of MSMEs through five key elements: quality visual content, consistency of publications, active consumer interaction, use of digital platform features, and customer testimonials. Storytelling and product education approaches have also been proven to be more effective in increasing engagement than conventional promotions. However, limitations in digital literacy, technical capabilities, and time management remain major obstacles. Originality - This study integrates visual content analysis, branding consistency, interactivity, and storytelling as a qualitative framework for MSME digital marketing strategies and emphasizes digital human resource capacity building as a key factor for its successful implementation.